2022
DOI: 10.24191/apmaj.v17i1-11
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Utilization of Audit Technology in Influencing Audit Job Performance

Abstract: Many traditional approaches of accounting and auditing assessment have been transformed by the growth of audit technology. This study aimed to identify key factors driving auditors’ adoption of audit technology in a developing country, Malaysia, through the lens of the Technology to Performance Chain (TPC) framework. The results of this study are based on a survey conducted in Malaysia with audit firms of varying sizes and were analyzed using the Structural Equation Modelling-Partial Least Square (PLS) statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It includes IT system usability, interface simplicity, and implementation assistance (Alkebsi & Aziz, 2017). As smooth and hassle-free integration is desirable, auditors are more inclined to embrace technology when they find it easy to use and are encouraged by its implementation (Noor, et al, 2022). Knight & Burns examine users' perceptions of ongoing technology use.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…It includes IT system usability, interface simplicity, and implementation assistance (Alkebsi & Aziz, 2017). As smooth and hassle-free integration is desirable, auditors are more inclined to embrace technology when they find it easy to use and are encouraged by its implementation (Noor, et al, 2022). Knight & Burns examine users' perceptions of ongoing technology use.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The incorporation of IT tools can automate routine tasks, facilitate data analysis, improve the identification of risks, and streamline the overall audit process (Al-Hiyari, 2019). As government agencies strive to enhance their audit capabilities and ensure the effectiveness of their internal audit department, understanding the factors that influence IT adoption becomes imperative (Noor, et al, 2022). These factors encompass a wide array of organizational, individual, and contextual elements, and comprehending their interplay is essential for optimizing IT adoption processes (Al-Hiyari, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently shown that this factor has a significant effect on how employees perceive the benefits they receive from their work environment (Kossek et al, 2011;Zheng et al, 2018). For example, a study by Noor et al (2022) found that organizational factor significantly affects perceived benefit. Awuah et al (2022) and Al-Okaily et al (2022) found that organizational factor significantly affects ITIA adoption.…”
Section: Organizational Factormentioning
confidence: 99%